The mixed gold-palladium polyoxo-noble-metalate [NaAuIII 4PdII8O8(AsO4) 8]11- - Izarova, Natalya V.; Kondinski, Aleksandar; Vankova, Nina; Heine, Thomas; Jaeger, Patrick; Schinle, Florian; Hampe, Oliver; Kortz, Ulrich (Chemistry - A European Journal, 2014)
The first fully inorganic, discrete gold-palladium-oxo complex [NaAu III4PdII8O8(AsO 4)8]11- has been synthesized in aqueous medium. The combination of single-crystal XRD, elemental analysis, mass spectrometry, and DFT calculations allowed establishing the structure and composition of the novel polyanion, and UV/Vis studies suggest that it is stable in neutral aqueous media. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: density functional calculations; gold; mass spectrometry; palladium; polyoxometalates